Γ-Ray dose dependent conductivity of MoS2 nanomaterials at different temperatures. Issue 44 (23rd October 2019) - He, Yupu; Xiang, Xia; Wu, Zhonglin; Li, Menglu; Deng, Hongxiang; Zhang, Jihua; Yang, Guixia; Chen, Hua; Yuan, Yonggang; Zu, Xiaotao
Abstract : The conductivity of γ-ray irradiated MoS2 nanomaterials depends on the service temperature. The proper γ-ray irradiation dose can significantly improve the conductivity of MoS2 when used at room temperature. Abstract : In this work, MoS2 nanomaterials were successfully prepared by a simple hydrothermal method. The samples were irradiated with the Co-60 gamma radioisotope at doses of 1, 10, 100, and 1000 kGy, and they were characterised by several analysis techniques. X-ray photoelectron spectroscopy (XPS) analysis showed that γ-ray irradiation did not change the stoichiometric ratio or charge state of MoS2 . The X-ray diffraction (XRD) patterns of the irradiated samples showed better crystallinity and decreased average grain size. The transmission electron microscopy (TEM) results also confirmed that MoS2 had better crystallinity after γ-ray irradiation. Raman analysis showed a red-shift of both E12g and A1g modes after γ-ray irradiation. The conductivities of the samples before and after irradiation were investigated at different temperatures. As the test temperature ( T ) increased, the conductivity of MoS2 monotonously decreased, and it did not change above 250 °C. When T < 100 °C, the conductivity first increased and then decreased with increasing γ-ray dose, reaching a maximum at 10 kGy. When T > 100 °C, the conductivity first decreased and then increased, reaching a minimum at 1 kGy. It is worth noting that the conductivity of the MoS2 nanomaterials was 511.956 S m −1 at 10 kGy γ-ray irradiation at 25 °C, which is almost 6.2 times that of the unirradiated sample at this temperature. This indicates that the conductivity of MoS2 nanomaterials strongly depends on the γ-ray dose and the service temperature. The appropriate dose of γ-ray irradiation can significantly improve the conductivity of MoS2 when used at room temperature.